How Spiritual Capital Motivates Purpose-Driven Leadership in a Profit-Driven World - Lusk, Carol (Journal of management, spirituality & religion, 2026)
In the face of significant societal challenges, the role of religiosity and spirituality has been scrutinized. Yet, in the management literature, these forms of spiritual capital remain underexplored. This qualitative study examined the role of spiritual capital during the leadership journey. We conducted narrative interviews with organizational leaders, exploring their life and career histories. Several key themes emerged, including a continuum of spiritual capital in the workplace, the manifestation of spiritual capital in motivation and leadership attainment, the sacred/secular divide as influencing the expression of faith, and the importance of a mission-aligned organizational purpose as a facilitator for motivating highly religious employees to take on leadership roles. Findings reveal the importance of spiritual capital and purpose in a profit-driven world.